Transformation of Human Resource Management practices under COVID-19 crisis: employee engagement and motivation - Aldash, A.; Kozhamzhar, G.; Namerov, A. (International School of Economics KAZGUU, Nur-Sultan, 2022)
The coronavirus pandemic has affected everyone and, therefore, is primarily considered as a human crisis. The lack of live communication, physical office and workspace affected the fact that employees stopped feeling involved in the workflow. All processes were transferred to an online format, companies experienced shock and uncertainty about how to manage people, their motivation and involvement remotely. This research allows us to understand how companies remotely maintain motivation and manage employee engagement and effectiveness. For this study qualitative and quantitative research methods were used in the form of semi-structured interviews and convenience sampling survey among Kazakhstani HR-managers and employees appropriately. As a result, it became clear that motivation among employees increased only at the very beginning of the pandemic, workers saw a wide range of advantages from the new work format. However, when the negative sides appeared in the form of blurred boundaries, household barriers, lack of self-discipline and communication with colleagues, there was stress and stagnation in productivity and motivation of employees. Therefore, summing up, the results of the study showed that motivation during the pandemic period fell down gradually and the transformation of HR practices became the outcome of this.
Keywords: Human Resource Management, remote work, motivation, engagement, pandemic, Kazakhstan